2019
DOI: 10.1002/pat.4609
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of poly (1‐vinyl‐3‐butylimidazolium‐co‐methyl methacrylate) gel polymer electrolytes for dye‐sensitized solar cells: Effect of structure and composition

Abstract: Herein, three ionic liquid random copolymers (P) containing 1‐vinyl‐3‐butylimidazolium bromide (VBImBr) and methyl methacrylate (MMA) with various molar ratios were prepared using conventional free radical polymerization. Afterward, their corresponding chemically cross‐linked copolymers (XP) were formed similarly in the presence of polyethylene glycol dimethacrylate (PEGDMA). The synthesized copolymers were characterized using FT‐IR, 1H NMR, and GPC. Differential scanning calorimetry (DSC) and thermal gravimet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 53 publications
(110 reference statements)
0
5
0
Order By: Relevance
“…It could be seen that the intensity of the peak increased with increasing content of VBIMBr, indicating the formation of a large number of hydrogen bonds. The peaks at 2935 and 2875 cm −1 can be assigned to –CH 3 and –CH 2 in-plane stretching of alkyl groups, 61 and the intensity of the double peaks increased with increasing VBIMBr content. The absorption peak at around 1647 cm −1 was attributed to the –CO asymmetric stretching vibration of the acrylamide unit, and the location of the peak gradually shifts to 1657 cm −1 in the spectrum of the PC 1 PAV 30 hydrogel with increasing addition of VBIMBr.…”
Section: Resultsmentioning
confidence: 98%
“…It could be seen that the intensity of the peak increased with increasing content of VBIMBr, indicating the formation of a large number of hydrogen bonds. The peaks at 2935 and 2875 cm −1 can be assigned to –CH 3 and –CH 2 in-plane stretching of alkyl groups, 61 and the intensity of the double peaks increased with increasing VBIMBr content. The absorption peak at around 1647 cm −1 was attributed to the –CO asymmetric stretching vibration of the acrylamide unit, and the location of the peak gradually shifts to 1657 cm −1 in the spectrum of the PC 1 PAV 30 hydrogel with increasing addition of VBIMBr.…”
Section: Resultsmentioning
confidence: 98%
“…Compared with SiO 2 , SiO 2 @MPS showed a characteristic peak of CO stretching vibration at 1716 cm –1 , which originated from the modification of the silane coupling agent . For SiO 2 @MPS@MIPs-MFM and SiO 2 @MPS@NIPs-MFM samples, the peaks at 1456 and 1549 cm –1 were ascribed to the deformation and stretching vibration of the imidazolium ring, indicating the successful grafting polymerization of MFM. , The surface elemental composition of SiO 2 @MPS, SiO 2 @MPS@MIPs-MFM, and SiO 2 @MPS@NIPs-MFM was further determined by XPS analysis. It can be seen from Figure B that the SiO 2 @MPS microsphere contained only Si, O, and C elements, whereas both MIPs and NIPs showed new signals at 399.6, 130.6, 255.2, 69.1, 198.7, 229.1, and 164.0 eV, which were attributed to the characteristic peaks of N 1s, P 2p, Br 3s, 3d, Cl 2p, S 2s, and 2p, respectively. ,, In addition, thermogravimetric analysis (TGA) results in Figure C also showed that SiO 2 @MPS@MIPs-MFM and SiO 2 @MPS@NIPs-MFM had higher weight loss than the bare SiO 2 @MPS microsphere in the temperature range from 100 to 600 °C, which may be caused by the decomposition of the polymer layer .…”
Section: Resultsmentioning
confidence: 97%
“…Block MFM and their precursors with different chemical structures were first characterized by 1 H NMR spectra. As shown in Figure A, the curve (a) of macro-CTA showed the characteristic peaks of the ionized imidazolium ring and the butyl group, corresponding to the signals at 9.2–7.2 ppm (peaks 3–5), 4.1 ppm (peak 6), and 1.8–0.8 ppm (peaks 7–9), respectively. After copolymerization with VIM and MPC in the second block segment, curve (b) of precursor 1 showed new characteristic peaks of the imidazole ring and methyl groups of quaternary ammonium salt at 7.1–6.4 (peaks 12–14) and 3.2 ppm (peak 21), respectively. , Compared with precursor 1 , new signals in curve (c) of MFM-1 appeared at 5.8 and 5.4 ppm (peak 25), which was attributed to the protons of the vinyl group . In addition, the peak intensity at 7.7–7.4 ppm in curve (c) representing the protons in the benzene ring (peak 23) increased significantly, demonstrating the successful alkylation of VBC on precursor 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Then, using PMMA‐CTA as macromolecular CTA, DMAEMA as monomer for the precursor QASs, EGDMA as crosslinking agent, PMMA‐b‐P(DMAEMA‐co‐EGDMA) (PM‐PDE), a novel crosslinked block copolymer was continued to be synthesized by RAFT polymerization. Therein, DMAEMA was selected as the cationic precursor because it helps to adjust the rigidity and stability of the polymer chain and block copolymers occur more easily than cationic compounds 35 . Using EGDMA as a crosslinking agent, it can effectively improve the mechanical properties and crosslinking density of the polymer chain.…”
Section: Resultsmentioning
confidence: 99%
“…Therein, DMAEMA was selected as the cationic precursor because it helps to adjust the rigidity and stability of the polymer chain and block copolymers occur more easily than cationic compounds. 35 Using EGDMA as a crosslinking agent, it can effectively improve the mechanical properties and crosslinking density of the polymer chain.…”
Section: Synthesis Of Polymer Cations-adjustable Porous Materialsmentioning
confidence: 99%